Compensation Management And Employee Retention Of Selected Commercial Banks In Anambra State, Nigeria - Chiekezie, Obianuju Mary; Emejulu, Gerald; Nwanneka, Aniekwe (Archives of Business Research, 2017)
This study was necessitated due to rate of employee turnover, which is increasing in Nigeria banking system; a situation whereby employee continuously move from one bank to another in a short period of time. This paper seeks to examine the influence of compensation management on employee retention. It specifically set out to examine the relationship between Salary and Employee satisfaction in selected Commercial banks in Awka. The study employed descriptive research design. Primary source of data was the major instrument used for this study. 60 copies of questionnaire were administered to employees of selected commercial banks (First bank, Fidelity and Sterling bank); 56 were retrieved and they were all useful. Pearson’s Product Moment Correlation was used for the analyses. The findings revealed that there is a positive weak relationship between salary and employee satisfaction. This shows that employees were not satisfied despite their seemingly attractive salary. In view of the finding, the study concluded that if management fail to formulate, administer and implement a good compensation policies that would allow them retain their talented employee; these employee might leave their job if they find a better offer elsewhere. The researcher recommended among others that compensation structure should include new and enticing ways to motivate and retain employee with wide range of benefits other than salary.